2022
DOI: 10.3390/life12020290
|View full text |Cite
|
Sign up to set email alerts
|

Of Cockroaches and Symbionts: Recent Advances in the Characterization of the Relationship between Blattella germanica and Its Dual Symbiotic System

Abstract: Mutualistic stable symbioses are widespread in all groups of eukaryotes, especially in insects, where symbionts have played an essential role in their evolution. Many insects live in obligate relationship with different ecto- and endosymbiotic bacteria, which are needed to maintain their hosts’ fitness in their natural environment, to the point of even relying on them for survival. The case of cockroaches (Blattodea) is paradigmatic, as both symbiotic systems coexist in the same organism in two separated compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…We showed that in planthoppers, like in beetles, cockroaches, and other hemipterans, bacteriocytes/bacteriomes are usually distributed in the body cavity within fat body tissue, usually close to reproductive organs or intestine ( Buchner, 1965 ; Michalik et al, 2014a ; Michalik et al, 2014b ; Michalik et al, 2018a ; Michalik et al, 2018b ; Hirota et al, 2020 ; Latorre et al, 2022 ). In contrast, in Camponotus ants, Hippoboscoidea flies, and some sucking lice, bacteriocytes are directly associated with the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that in planthoppers, like in beetles, cockroaches, and other hemipterans, bacteriocytes/bacteriomes are usually distributed in the body cavity within fat body tissue, usually close to reproductive organs or intestine ( Buchner, 1965 ; Michalik et al, 2014a ; Michalik et al, 2014b ; Michalik et al, 2018a ; Michalik et al, 2018b ; Hirota et al, 2020 ; Latorre et al, 2022 ). In contrast, in Camponotus ants, Hippoboscoidea flies, and some sucking lice, bacteriocytes are directly associated with the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Monosymbiotic bacteriomes, bearing a single symbiont taxon and with relatively simple organization, are common in insects (Buchner, 1965). Some of the better-known examples include cockroaches (Blattobacterium), tsetse flies (Wigglesworthia), aphids (Buchnera), and scale insects (Tremblaya phenacola, Kotejella) (Rio et al, 2012;Michalik et al, 2014b;Michalik et al, 2018b;Michalik et al, 2019;Latorre et al, 2022). The less common are disymbiotic bacteriomes harboring two different types of microorganisms.…”
Section: A Snapshot Of the Diversity Of Anatomical Integration Patter...mentioning
confidence: 99%
“…The German cockroach Blattella germanica (Blattodea) is a good model to study these complex symbiotic relationships because two symbiotic systems coexist in a single individual: a bacterial obligate intracellular endosymbiont Blattabacterium cuenoti (hereinafter Blattabacterium) [14] and a rich and complex gut microbiota [15]. Blattabacterium, a Gramnegative bacterium belonging to the phylum Bacteroidetes, is vertically transmitted from mother to offspring through the infection of the oocytes in each generation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have shown that cockroaches are rich in microbes [ 3 , 4 , 16 , 18 ], and some of these microbes have formed an interdependent symbiotic relationship with the host during the long-term co-evolution process. Wolbachia is a gram-negative, maternally inherited, intracellular Rickettsia-like alphaproteobacterium that is found in many arthropods, such as insects, mites, ticks, arachnids, terrestrial crustaceans (Isopods) and filarial nematodes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%